Tourist Attractions of Batur Geotourism, Bali - ARJANA, I Wayan Basi; ERNAWATI, Ni Made; ASTAWA, I Ketut (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).23, 2020)
For the geotourism development to be success, it is imperative for management to recognise the specific needs of its market niche. This study aims at identifying geotourists’ needs, particularly in the aspect of tourist attraction which is the main part of tourism products by evaluating tourists’ perceptions on attractions at Batur geotourism in Bali in Indonesia. This is a qualitative study using in-depth interview as data collecting method. The respondents are international and domestic tourists who have visited Batur, selected using convenience sampling. Based on their preference of geotourism experiences, two types of geotourists are identified: ‘Professional-geoturists’ prefer to explore, take more challenging tracks, enjoy nature in seclusion, accept existing facilities, enjoy local foods and mingle with locals; whilst, “Amateur-geotourists“ are interested in fun-trekking choosing less challenging routes, enjoy nature with friends/families to have fun, prefer more developed facilities and variety of foods. Batur-climbing is the most popular, tourists do not know most other attractions; therefore, Batur attraction theme and image need strengthening by developing new and refining the existing attractions and communicate them through an integrated promotion program. The aspect of nature and local hospitality are identified to be preserved for locals and the authenticity of the attractions at the geotourism site. The changes expected are majoring in infrastructure with a blended to nature design as preference. The identification of geotourism attractions a case of Batur could be used as a reference by Batur stakeholder in developing the products. Text of the abstract: The abstract should summarize the content and conclusions of the paper in less 200 words, focusing on what your research is about, what methods have been used, and what you found out.